A Cross-Cultural Assessment of Three Theories of Pro-Environmental Behavior: A Comparison Between Business Students of Chile and the United States - Parada-Daza, V (2011)
We surveyed business students in the United States (n = 256) and Chile (n = 310) to compare three theories of pro-environmental behavior.We examined Ajzen and Fishbein s theory of reasoned action, Schawartz s norm activation theory, and the values-beliefs-norms theory created by Stern, Dietz, Abel, Guagnano, and Kalof. We produced reliable measures for both samples. Each theory explained a significant amount of the variance in behavioral intention, although no theory clearly dominated for either the United States or Chile. However, among the variables included among these theories, the norms variable consistently produced the strongest relationship with behavioral intention. We discuss avenues of future research focusing on norms and more parsimonious combinations of the variables across these three theories. © The Author(s) 2011.